Potential risks of early specialization and high training volume among elite youth football players in Chinese school football - Feng, R.; Gómez, M.; García-de-Alcaraz, A.; Li, X.; Li, C. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
Introduction: With China`s commitment to promoting youth football in schools, more and more players engage in more frequent, intensive and organized sports training from a young age despite the controversy over early specialization (ES). Supporters claim that ES allows players gain advantages in the competition, better training resources and career opportunities, but some literature on youth sports link ES with burnout and injuries. Therefore, this research aims to investigate the correlation between the training volume and ES level of elite Chinese youth players and potential risks of ES.